2016
DOI: 10.3767/003158516x692149
|View full text |Cite
|
Sign up to set email alerts
|

Pyricularia graminis-tritici, a new Pyricularia species causing wheat blast

Abstract: Pyricularia oryzae is a species complex that causes blast disease on more than 50 species of poaceous plants. Pyricularia oryzae has a worldwide distribution as a rice pathogen and in the last 30 years emerged as an important wheat pathogen in southern Brazil. We conducted phylogenetic analyses using 10 housekeeping loci for 128 isolates of P. oryzae sampled from sympatric populations of wheat, rice, and grasses growing in or near wheat fields. Phylogenetic analyses grouped the isolates into three major clades… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
94
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 56 publications
5
94
0
1
Order By: Relevance
“…Using population and phylogenomic analyses of single-copy orthologous genes and whole-genome SNPs identified in M. oryzae genomes from multiple cereal and grass hosts, we provide evidence that M. oryzae is subdivided into multiple lineages preferentially associated with one host plant genus. Neither the reanalysis of previous data nor the analysis of new data using previous phylogenetic species recognition markers supports the existence of a wheat blast-associated species called P. graminis-tritici (24). Marker MPG1, which holds most of the divergence previously detected, does not stand as a diagnostic marker of the wheat-infecting lineage of M. oryzae when tested in other lineages.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Using population and phylogenomic analyses of single-copy orthologous genes and whole-genome SNPs identified in M. oryzae genomes from multiple cereal and grass hosts, we provide evidence that M. oryzae is subdivided into multiple lineages preferentially associated with one host plant genus. Neither the reanalysis of previous data nor the analysis of new data using previous phylogenetic species recognition markers supports the existence of a wheat blast-associated species called P. graminis-tritici (24). Marker MPG1, which holds most of the divergence previously detected, does not stand as a diagnostic marker of the wheat-infecting lineage of M. oryzae when tested in other lineages.…”
Section: Discussionmentioning
confidence: 96%
“…All of the P. graminis-tritici isolates from the Castroagudin et al study were contained in a clade with 80% support. Inspection of the MPG1 marker that was reported to be diagnostic for P. graminis-tritici (Castroagudin et al [24]) revealed that all of the isolates in this clade contained the P. graminis-tritici-type allele (green dots) and should therefore be classified as P. graministritici (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations